Gender, Space and Place: The Experience of Servants in Rural Households 1550-1750 - Flather, Amanda (2017)
This article examines the organisation and use of domestic space by servants for eating and sleeping, looking particularly at the seventeenth century and at middling sort households, broadly defined. It relates models of architectural and social change to the ways that individuals described their experience and use of domestic space in court records. It concludes that while there was a trend to separate the work and living spaces of servants from the rest of the family, an early modern house was not one where rigid and static social patterns were mapped upon its spaces. A number of social factors struggled to define the social character of a space, a struggle which largely pivoted around the concepts of control and use rather than separation or segregation according to status or gender. Spatial patterns were ephemeral. Nonetheless, it is possible to illustrate how some aspects of the social relations of the household were reflected in and reinforced by the way that domestic space was organised and used. Moreover, the implications of such use and organisation carry important messages about the nature of the household itself.